1995
DOI: 10.1039/ft9959102877
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of intra-polymer electron-transfer reactions in macromolecule–metal complexes

Abstract: A macromolecul~metal complex with redox centres on the same polymer chain of partially quaternized poly(1vinylimidazole) (QPVlm) has been designed. In this complex, Co(tfacacen) (tfacacen = N,N'-ethylenebis(l,l,ltrifluoro-4-iminopentan-2-one), a Cot'-Schiff base complex, and quaternized imidazolium residues, an oxidizing agent, are both linked to a polymer backbone. The mechanism of the electron-transfer reaction between Co(tfacacen) and the quaternized imidazolium residue on this macromolecular complex have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…27 To address this issue, we carried out studies to optimize the spacer length between LPEI and the ferrocene moiety, as previous studies had shown that extending the redox center away from the polymer backbone could improve the performance of the sensors by increasing the electron diffusion rates. 5,28,29 This study showed that a 6-carbon spacer ͑Fc-C 6 -LPEI͒ improved the stability while reducing the maximum current density ͑ j max ͒ of the sensors, while a polymer with a 3-carbon spacer ͑Fc-C 3 -LPEI͒ both improved the stability and produced a j max of approximately 1 mA/cm 2 . 27 The high current densities obtained with these polymers led us to investigate the possibility of using them as materials for biofuel cell anodes.…”
mentioning
confidence: 94%
“…27 To address this issue, we carried out studies to optimize the spacer length between LPEI and the ferrocene moiety, as previous studies had shown that extending the redox center away from the polymer backbone could improve the performance of the sensors by increasing the electron diffusion rates. 5,28,29 This study showed that a 6-carbon spacer ͑Fc-C 6 -LPEI͒ improved the stability while reducing the maximum current density ͑ j max ͒ of the sensors, while a polymer with a 3-carbon spacer ͑Fc-C 3 -LPEI͒ both improved the stability and produced a j max of approximately 1 mA/cm 2 . 27 The high current densities obtained with these polymers led us to investigate the possibility of using them as materials for biofuel cell anodes.…”
mentioning
confidence: 94%
“…The imidazole ligand is of particular interest due to its important role in many biological systems, especially as the side group in histidine which plays an essential role in the active motif of many enzymes [7]. Imidazole in polymers has traditionally been utilized in a variety of applications such as immobilized catalysts [8,9], redox reactions [10], water purification [11,12], hydrometallurgy/metal recovery [13,14], and ion and proton conductors [15].…”
Section: Introductionmentioning
confidence: 99%
“…The imidazole ligand is of particular interest due to its important role in many biological systems, especially as the side group in histidine which plays an essential role in the active motif of many enzymes [8]. Imidazole in synthetic polymers and biopolymers has traditionally been utilised in a variety of applications such as immobilised catalysts [9,10], redox reactions [11], water purification [12,13], hydrometallurgy/metal recovery [14,15], ion and proton conductors [16], chelating resin adsorbents [12][13][14][15] etc. The majority of the these applications and functions exploit the fact that the imidazole group is very strongly and selectively coordinated by metal ions, in particular Cu(II) and Zn(II) [8].…”
Section: Introductionmentioning
confidence: 99%
“…the pyrrole nitrogen (see Scheme 1), e.g. poly (1-vinylimidazole) or poly(N-vinylimidazole) [11,[20][21][22][23], since the monomer is synthesised by attaching the vinyl group to the electronegative pyrrole nitrogen [24]. However in histidine, the most common naturally existing type of imidazole ligand, the imidazole is attached at the 4 th position C 4 , leaving the pyrrole nitrogen unsubstituted.…”
Section: Introductionmentioning
confidence: 99%